A bioinspired flexible organic artificial afferent nerve - Kim, Yeongin; Chortos, Alex; Xu, Wentao; Liu, Yuxin; Oh, Jin Young; Son, Donghee; Kang, Jiheong; Foudeh, Amir M.; Zhu, Chenxin; Lee, Yeongjun; Niu, Simiao; Liu, Jia; et al. (Science (American Association for the Advancement of Science), 2018)
Sensory (or afferent) nerves bring sensations of touch, pain, or temperature variation to the central nervous system and brain. Using the tools and materials of organic electronics, Kim et al. combined a pressure sensor, a ring oscillator, and an ion gel–gated transistor to form an artificial mechanoreceptor (see the Perspective by Bartolozzi). The combination allows for the sensing of multiple pressure inputs, which can be converted into a sensor signal and used to drive the motion of a cockroach leg in an oscillatory pattern. Science , this issue p. 998 ; see also p. 966 Organic flexible electronics mimic the functions of a biological afferent nerve and actuate muscles. The distributed network of receptors, neurons, and synapses in the somatosensory system efficiently processes complex tactile information. We used flexible organic electronics to mimic the functions of a sensory nerve. Our artificial afferent nerve collects pressure information (1 to 80 kilopascals) from clusters of pressure sensors, converts the pressure information into action potentials (0 to 100 hertz) by using ring oscillators, and integrates the action potentials from multiple ring oscillators with a synaptic transistor. Biomimetic hierarchical structures can detect movement of an object, combine simultaneous pressure inputs, and distinguish braille characters. Furthermore, we connected our artificial afferent nerve to motor nerves to construct a hybrid bioelectronic reflex arc to actuate muscles. Our system has potential applications in neurorobotics and neuroprosthetics.